Thermal ablation of malignant lung tumors - Schneider, Thomas; Heußel, Claus Peter; Herth, Felix; Dienemann, Hendrik (Deutsches Ärzteblatt, 2013)
Background: About 50 000 new cases of non-small-cell carcinoma of the lung are diagnosed in Germany each year. More than 20% of the affected patients cannot be offered radical resection because of comorbidity alone. The lung is also the second most common site of distant metastases of extrathoracic tumors; it is the only site of such metastases in 20% of cases. In recent years, image-guided thermoablation has been used with increasing frequency in patients who are unable to undergo surgery for medical reasons. Methods: The PubMed database was selectively searched for publications on the indications, complications, and results of the thermoablative techniques currently in clinical use, with special attention to radiofrequency ablation (RFA). Results: There is only a small evidence base to date concerning the treatment of malignant lung tumors with thermoablation. Retrospective and prospective case series have been published, but no randomized controlled trials have yet been conducted. RFA, the most common technique, involves the image-guided percutaneous placement of one or more probes in the tumor, to which thermal energy is then applied. For peripherally located tumors that measure less than 3 cm in diameter, local control of tumor growth can be achieved in about 90% of cases. The long-term results that are now available from smaller series provisionally indicate 5-year survival rates of 20% to 61%. The most common complication is pneumothorax requiring drainage, which occurs in about 10% of cases. In the intermediate term, thermoablation does not cause any clinically relevant loss of pulmonary function. Conclusion: Image-guided thermoablation cannot now be considered an alternative to surgery for the treatment of malignant lung tumors with curative intent. It does, however, widen the spectrum of therapeutic options for patients who are medically unable to undergo a surgical procedure.